Pengujian Operasional untuk Mengetahui Potensi Kerusakan pada Indikator Mesin Laser Cuting Engraving Dioda 15 Watt - Wulandari; Sairul Effendi; Almadora Anwar Sani (Bulletin of Community Engagement, 2024)
This study aims to analyze the potential damage that occurs in the laser cutting engraving machine indicator using a 15 watt diode. The data analysis method in this study adopts a quantitative approach with an experimental design, focusing on a laser cutting engraving machine using a 15 watt diode. Operational testing was carried out through a series of simulations and direct trials on the machine to identify possible damage points and the factors that influence them. By utilizing the real-time performance monitoring method, this study successfully identified several potential damages that were directly related to the stability of the electric current and the duration of use of the machine. These findings are expected to be a reference in improving the reliability of laser cutting engraving machines, as well as reducing the risk of future damage through improving operational procedures and machine maintenance.